STUDI KORELASIONAL ANTARA DISIPLIN KERJA TERHADAP TINGKAT KINERJA KARYAWAN (STUDI KASUS PESERTA MAGANG LPK MEI ) - Pupung Purnamasari; Ade Sofyan (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted from August 2021 to December 2021. The research method used in this study is a descriptive and quantitative analysis method. The number of samples is 37 respondents of KAP MEI Apprentice employees. Data analysis was carried out using simple regression analysis and pearson correlation coefficient analysis. With a simple regression analysis the authors buy goods that can be used to predict the level of employee performance through work discipline variables in the research object. The regression obtained is the regression equation which can be used to predict the Y variable, namely the level of employee performance through the X variable, namely work discipline, Y = 15.251 + 0.379X. The a value is 15,251, meaning that if there is no work discipline variable (X), then the employee's performance (Y) is already 15,251. Then the work discipline variable has a positive b that is equal to 0.379, meaning that the correlation of work discipline has a positive influence or is directly proportional to the performance of the LPK MEI apprentice employees. This implies that if work discipline increases by 0.379, employee performance will increase by 0.379 and vice versa. The second method is the correlation coefficient method which aims to determine the level of relationship between variable X and variable Y. In this study, a correlation of (r) = 0.599 was obtained. This shows that the correlation level of work discipline has a positive and moderate effect on employee performance. Meanwhile, from the calculation of the coefficient of determination (Kd) = 35.9%. This shows that work discipline contributes to employee performance by 35.9% and the remaining 64.1% is influenced by other factors. The results of the significance test (t test) obtained a value of 4.432 while the t table was 1.687. The result is tcount > ttable, thus H1 is accepted and H0 is rejected. So it can be concluded that there is an influence between work discipline on the performance of LPK MEI apprentices.